Individual and organizational factors influencing career aspiration of hotel managers - Mohamad, Meliza; Mohd Rasdi, Roziah (2014)
This study aims to examine the factors influencing the career aspiration of managers at the selected hotels. Using descriptive correlational approach, this study involved 162 managers from 11 5-star international hotels and resorts in Malaysia. The findings of this study revealed that the managers’ career aspiration was explained by different aspects of variables. The research revealed that the overall level of managers’ career aspirations was high, and generally the levels of the managers’ individual-related variables and organizational-related variables were also high. The correlation results indicated that commitment, self-efficacy, extraversion and perceived organizational support were correlated with the managers’ career aspiration except for the conscientiousness and organizational socialization. The implications for research and practice are highlighted.